The Old and the Stubborn? Firm Characteristics and Relocation in the Netherlands - Brouwer, Aleid E. (European Spatial Research and Policy, 2010)
This study gives some insight into the relationships between the spatial environment, firm characteristics and long term existence of firms in the Netherlands. A logit model is employed to investigate the locational difference of firms, considering firm characteristics such as age, size, region and network. The main findings are that (long-term) continuation of the location and firm size are positively associated with long-term existence of firms.